SEMIOTIC IN SALAH PIKNIK POETRY BY JOKO PINURBO’S - Dzarna; Hasan Suaedi; Isti'anah (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
The purpose of this study is to describe semiotic analysis on Picnic Poetry that has iconic meaning of icon, index, and symbols. This type of research is a qualitative descriptive, because the data and results of this study are dominant in the form of words. Data collection techniques using documentation methods. In this study, the signs contained in poetry are interesting discussions to analyze. The signs found in the poem are not found at random, but are examined repeatedly until the signs found are true. . The results of the data analysis showed a semiotic contained in Karya Picnic Work Joko Pinurbo. The results of the data analysis showed a semiotic contained in Picnic Poetry includes (1) sadness, (2) life, (3) excitement, (4) excited, (5) shocked. Based on the results of the data, the conclusion of the study, namely by the analysis of semiotic analysis in the poem, readers will understand the various signs in the Picnic Work Joko pinurbo poem that contains the phenomenon that occurs in the new corona outbreak that hit the world, also marked by humor and game of words, containing satire and criticism of the government. Keywords: Poetry, Icon, Index, And Symbols